2021
DOI: 10.1590/1981-86372021001720200145
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Painful Temporomandibular Disorders: what does the dentist need to know?

Abstract: COVID-19 outbreak may lead to major impacts in applied oral sciences. Remarkably, it could be expected that factors associated to pandemic may lead to a greater risk of developing, worsening and perpetuating TMD and its associated risk factors. This non systematic literature review aims to discuss how the COVID-19 pandemic can influence the emergence, maintenance or worsening of TMD worldwide. During epidemics: the number of people whose mental health is affected tends to be greater than the number affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The COVID-19 pandemic, multiple lockdowns, and home confinement measures have had many negative and harmful effects, not only on the worldwide economy but also on mental and physical health. Several studies have concluded worsening or aggravation of TMD symptoms due to the pandemic as a result of stress and psychosocial impacts [5,6,[10][11][12][13][14][18][19][20][21][22], but to our knowledge, none has yet investigated TMDs as a possible symptom of COVID-19 infection; therefore, we chose to conduct a survey to assess the prevalence of TMD onset or aggravation of previous symptoms and determine possible predictors affecting this prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic, multiple lockdowns, and home confinement measures have had many negative and harmful effects, not only on the worldwide economy but also on mental and physical health. Several studies have concluded worsening or aggravation of TMD symptoms due to the pandemic as a result of stress and psychosocial impacts [5,6,[10][11][12][13][14][18][19][20][21][22], but to our knowledge, none has yet investigated TMDs as a possible symptom of COVID-19 infection; therefore, we chose to conduct a survey to assess the prevalence of TMD onset or aggravation of previous symptoms and determine possible predictors affecting this prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The most common signs of TMDs are localized jaw pain, restricted jaw movement, and TMJ sounds during mandibular movements, and the 12 common disorders include arthralgia, myalgia, local myalgia, myofascial pain, myofascial pain with referral, four-disc displacement disorders, degenerative joint disease, subluxation, and headache attributed to TMDs [8,9]. Psychological factors are considered sufficient to provoke, worsen, and maintain these symptoms during COVID-19 infection and after it [10][11][12]; investigating the prevalence of these symptoms during infection is important to outline clinical strategies for patient care [12][13][14][15]. During the pandemic, an increase in TMD symptoms in infected patients was noticed in daily practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation